Intimate Partner Violence Among Male and Female U.S. Community College Students - Benson, Shakiera (2007)
Intimate partner violence affects a significant portion of college-aged individuals, but researchers know little about how the intersection of age, race, class, and gender influence intimate partner violence among community college students in the United States. In this quantitative correlational study, I examined the relationship between intimate partner violence and gender, race, age, class, marital status, and past abuse among community college students using the intersectionality theory. I used the Abusive Behavior Inventory and a demographic survey to collect data via a convenience sample of the target population of men (n = 220) and women (n = 330) attending a community college or recent graduates. Multiple linear regression analysis indicated although no demographic variables were related to the frequency of psychological violence, lower age and higher socioeconomic status were related to increased frequency of physical violence. Individuals aged 18-24 were more likely than other groups to experience physical violence (t = -2.73, p = .008), and individuals with higher income levels (larger than $50,000) were more likely than individuals in other socioeconomic statuses to experience physical violence (t = 1.99, p = .049). The implications for positive social change include generating data regarding the potential predictive demographic factors that influence intimate partner violence, which may help professional's complete interventions that address intimate partner violence among community college students. More targeted interventions could reduce the rate of intimate partner violence and the long-term effects of intimate partner violence, particularly among the unexpected populations affected by intimate partner violence, as I indicated